2021
DOI: 10.3389/fmolb.2021.633590
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Predictive Model for Early Refractoriness of Transarterial Chemoembolization in Patients With Hepatocellular Carcinoma

Abstract: Objectives: To develop and validate a predictive model for early refractoriness of transarterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC).Methods: In this multicenter retrospective study, a total of 204 consecutive patients who initially underwent TACE were included. Early TACE refractoriness was defined as patients presented with TACE refractoriness after initial two consecutive TACE procedures. Of all patients, 147 patients (approximately 70%) were assigned to a training set, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A recent study showed a higher propensity of TACE refractoriness in patients with BCLC-B HCC beyond the Milan and the up-to-7 criteria [ 33 ]. Other studies also demonstrated that tumors beyond the up-to-7 criteria were significantly related to early TACE refractoriness in patients with BCLC-B HCC [ 32 , 34 ]. Second, liver function reserve tends to deteriorate after TACE in patients with HCC beyond the up-to-7 criteria [ 33 , 35 ] because they may need multiple cycles of TACE.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed a higher propensity of TACE refractoriness in patients with BCLC-B HCC beyond the Milan and the up-to-7 criteria [ 33 ]. Other studies also demonstrated that tumors beyond the up-to-7 criteria were significantly related to early TACE refractoriness in patients with BCLC-B HCC [ 32 , 34 ]. Second, liver function reserve tends to deteriorate after TACE in patients with HCC beyond the up-to-7 criteria [ 33 , 35 ] because they may need multiple cycles of TACE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested patients with tumor burden beyond the up-to-seven criteria are unlikely to respond to TACE and their hepatic reserve tends to deteriorate after treatment (13,14). Recently, Wang et al showed that patients who were early refractory to TACE had significantly worse prognoses (PFS: 4.36 months vs. 12.2 months) than those responded to treatment (15). Similarly, our patient cohort had extensive tumor burden and most became refractory to TACE after median of two sessions; hence, the prognosis of matched-TACE arm was poor with median PFS 4.83 months, which is similar with the literature (15).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recently, Wang et al showed that patients who were early refractory to TACE had significantly worse prognoses (PFS: 4.36 months vs. 12.2 months) than those responded to treatment (15). Similarly, our patient cohort had extensive tumor burden and most became refractory to TACE after median of two sessions; hence, the prognosis of matched-TACE arm was poor with median PFS 4.83 months, which is similar with the literature (15). Our study had provided a novel therapeutic approach for those who respond poorly to TACE.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“… 13 , 14 The revised definition of TACE refractoriness by JSH has been accepted into clinical treatment guidelines in some Asian regions and serves as the key factor for terminating TACE treatment. Patients who develop TACE refractoriness after two consecutive TACE sessions, which is called early TACE refractoriness, 15 may have a different survival compared with patients who develop TACE-refractoriness after more TACE treatments. A multicenter retrospective study found that the tumor response rate to a third TACE treatment was 58.3% and 48% in patients with stable tumors after the second TACE session of two cohorts.…”
Section: Introductionmentioning
confidence: 99%